Hubungan Self Efficacy, Pelibatan Orang Tua, dan Self Determination Dengan Kemandirian Belajar Peserta Didik - Sherrin nurlita Wwidya; Arbin Janu Setiyowati; Adi Atmoko (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2023)
Independent learning is one of the main factors in the success of students. This study aims to determine the correlation between self-efficacy, parental involvement, and self-determination with the learning independence of high school Surabaya students. The correlational design involved 390 samples. Data were collected through four scales with item validity test ≥ 0.3 and Cronbach Alpha reliability of 0.6 - 0.770, then analyzed by multiple linear regression. The regression results show that (sig F (172) = 0.000 <0.05) there is a simultaneous significant correlation between self-efficacy, parental involvement, and self-determination with learning independence. The contribution of the three predictors in the model together is 57.30% on learning independence.